Perceptions of Corporate Social Responsibility in the Pharmaceutical Industry after COVID-19 and Implications for Health-Conscious Tourism - Nemec Rudež, Helena; Rudež, Lana (Naše gospodarstvo/Our economy, 2025)
The paper examines the perception of Generation Z regarding the social corporate responsibility (CSR) of pharmaceutical companies after the COVID-19 pandemic, which increased health awareness. Using a structured online questionnaire conducted among students, the study sheds light on generational attitudes towards economic, social, and environmental dimensions of CSR in the pharmaceutical industry. The results show that the social dimensions, in particular good working conditions, are generally rated most favourably. CSR activities need to be supported by appropriate communication with stakeholders, with online information proving to be particularly influential for Generation Z. Furthermore, some CSR activities of the pharmaceutical industry go beyond this sector and could be reflected in health-conscious tourism.